Rancang Bangun Alat Penetas Telur Otomatis Kapasitas 50 Butir Mitra RAKTA FARM Desa Gelgel Klungkung-Bali - Dwikiarta, I Made Sastra; Prabhadika, I Putu Yudi (Lembaga Dongan Dosen, 2024)
This research aims to design and develop an automatic egg incubator with a capacity of 50 eggs, equipped with an automatic temperature and humidity control system. The methods used in this study include the design and construction of the incubator, testing, and performance evaluation at the partner site, RAKTA FARM in Gelgel Village, Klungkung-Bali. The incubator is designed using components such as the XH-W3001 Digital Thermostat and DH48S-S Digital Timer, allowing for automatic adjustment of temperature and humidity to ensure optimal hatching quality. The results show that the incubator can maintain a temperature range of 37.5°C to 38°C and humidity between 50% and 60%, with a hatching success rate of 95% after being tested over three batches. The development of this incubator is expected to enhance the efficiency of production and the quality of native chicken hatchlings, providing a solution for farmers in addressing the challenges of sustainable chicken population growth.